Search for the lepton flavor violating decay τ → 3μ in proton-proton collisions at √s = 13 TeV - CMS Collaboration; Damarseçkin, Serdal (Springer Science and Business Media Deutschland GmbH, 2021)
Results are reported from a search for the lepton flavor violating decay τ → 3μ in proton-proton collisions at s = 13 TeV. The data sample corresponds to an integrated luminosity of 33.2 fb−1 recorded by the CMS experiment at the LHC in 2016. The search exploits τ leptons produced in both W boson and heavy-flavor hadron decays. No significant excess above the expected background is observed. An upper limit on the branching fraction ℬ(τ → 3μ) of 8.0 × 10−8 at 90% confidence level is obtained, with an expected upper limit of 6.9 × 10−8.
Keywords: Hadron-Hadron scattering (experiments); Lepton production; Tau Physics